Access Guide to Human Proteinpedia. Issue 1 (1st March 2013) - Muthusamy, Babylakshmi; Thomas, Joji Kurian; Prasad, T.S. Keshava; Pandey, Akhilesh
Abstract: Human Proteinpedia (http://www.humanproteinpedia.org ) is a publicly available proteome repository for sharing human protein data derived from multiple experimental platforms. It incorporates diverse features of the human proteome including protein‐protein interactions, enzyme‐substrate relationships, PTMs, subcellular localization, and expression of proteins in various human tissues and cell lines in diverse biological conditions including diseases. Through a publicly distributed annotation system developed especially for proteomic data, investigators across the globe can upload, view, and edit proteomic data even before they are published. Inclusion of information on investigators and laboratories that generated the data, as well as visualization of tandem mass spectra, stained tissue sections, protein/peptide microarrays, fluorescent micrographs, and western blots, ensures quality of proteomic data assimilated in Human Proteinpedia. Many of the protein annotations submitted to Human Proteinpedia have also been made available to the scientific community through Human Protein Reference Database (http://www.hprd.org ), another resource developed by our group. In this protocol, we describe how to submit, edit, and retrieve proteomic data in Human Proteinpedia. Curr. Protoc. Bioinform . 41:1.21.1‐1.21.15. © 2013 by John Wiley & Sons, Inc.